Dispersion and sedimentation of titanium dioxide nanoparticles in freshwater algae and daphnia aquatic culture media in the presence of arsenate. Issue 1 (1st January 2018) - Wang, Zhenhong; Luo, Zhuanxi; Yan, Yamen
ABSTRACT: Little information is available on Titanium dioxide nanoparticles (nTiO2 ) behavior in different culture media for aquatic organisms. This study aimed to accurately evaluate nTiO2 dispersion and sedimentation in common freshwater algae (BG-11) and daphnia aquatic (SM7) culture media. We additionally investigated potential mechanisms of nTiO2 stability under arsenate influence. Results showed that high ionic strength in culture media was probably a key reason for the acute nTiO2 agglomeration found. Additionally, the hydrodynamic size of nTiO2 suspension in the presence of arsenate was significantly larger, increasing with arsenate concentration in ultrapure water. Conversely, the hydrodynamic size in BG-11 and SM7 decreased with arsenate concentration. The nTiO2 sedimentation rate increased significantly with arsenate concentration in ultrapure water but significantly decreased in BG-11 and SM7 culture media. Many nTiO2 remained suspended after initial rapid sedimentation and the slight sedimentation that occurred in the subsequent 24 h, suggesting that algae and daphnia within the water column will be exposed to small nanoparticle aggregates for a long period of time. Such nTiO2 behavior, especially in the presence of arsenate, requires more consideration than the different toxicological results reported in literature.